Deradicalization of Qur'an Exegesis in Islamic Boarding Schools in Central Java - Ma'mun Mu'min; Muhammad Syukron (LP2M IAIN kUDUS, 2021)
Since its establishment in the 13th century, Islamic boarding schools have played a key role in deradicalization using the exegesis of the Qur'an in Indonesia. The diversity of Islamic boarding schools is the result of the creativity of the ulama in acculturating the culture of the local Muslim community with the kyai as the main driver. As an Islamic educational institution, Islamic boarding schools integrate with the community in performing spiritual worship, educating, and integrating normative culture in religion. Islamic boarding schools create a harmonious, pluralist, and inclusive Muslim community. Nowadays, Islamic boarding schools face accusations from the West as an institution that produces radicals and terrorists. Bombings in Indonesia are mostly done by alumni of Islamic boarding schools. Bomb documents from JW Marriott and Ritz-Carlton hotels belonging to Jamaah Islamiyah (JI) contain information that 141 Islamic boarding schools and 388 Islamic leaders have joined JI. This study aims to complement the shortcomings of existing studies by highlighting the role of Islamic boarding schools in deradicalization using the exegesis of the Qur’an for students in Central Java so that they can avoid radicalism and terrorism. This study is crucial to answer negative accusations against Islamic boarding schools and encourage the creation of moderate exegeses. To elaborate on this effort, the researcher uses the social dialectical theory of Peter L. Berger and Thomas Luckmann, the concept of non-violent Islam from Abdurrahman Wahid, and the concept of Zamakhsyari Dhofier's Islamic boarding schools using socio-anthropological perspectives.